A comparative study of the effect of a gentle ketogenic diet containing medium-chain or long-chain triglycerides on chronic sleep deprivation-induced cognitive deficiency. Issue 4 (10th February 2022) - Wang, Xueyan; Yang, Yueqi; Xiao, Aiai; Zhang, Ning; Miao, Mingyong; Wang, Zhengping; Han, Jun; Wen, Min
Abstract : Medium-chain triglyceride-enriched KD exhibited stronger effects than the long-chain triglyceride-enriched KD on preventing chronic sleep deprivation-induced cognitive deficiency via suppressing ferroptosis and improving synaptic plasticity. Abstract : The ketogenic diet (KD) is well known for its neuroprotective effect, but little is known about its prophylactic efficacy against chronic sleep deprivation (SD) induced cognitive deficiency. An emerging study indicated that ferroptosis plays an important role in neurologic diseases but has been rarely reported in chronic SD. Here, we investigated the prophylactic effects of a medium-chain triglyceride-enriched KD (MKD) and a long-chain triglyceride-enriched KD (LKD) on cognitive deficiency and revealed the underlying mechanism focused on ferroptosis in chronic SD model mice. The results showed that the MKD exhibited stronger effects than the LKD on improving cognitive deficiency via suppressing ferroptosis and improving synaptic plasticity. Further mechanism results indicated that MKD produced higher Sirt3 protein levels than LKD, which probably contributed to the synergistic effect of beta hydroxybutyric acid and decanoic acid. Our finds provide novel evidence for the KD as a safe and feasible dietary intervention to prevent chronic SD-induced cognitive deficiency, and suggest a better choice of medium-chain fatty acid-enriched KD.